Sistem Pendukung Keputusan Untuk Pemilihan Kualitas Telur Bebek Di Kabupaten Nganjuk Menggunakan Metode SAW - Muhammad Najibullah Muzaki; Erna Daniati; Angga Pradipa Eko Widodo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The determination of duck egg quality among farmers and salted egg SMEs in Nganjuk Regency is still carried out manually based on experience, resulting in subjective, inconsistent, and time-consuming assessments. This condition causes the egg grading process to be less optimal and may affect the quality of products marketed. This study aims to design and develop a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to support a more objective, faster, and structured duck egg quality selection process. The system was developed using the Waterfall model, consisting of requirements analysis, system design, implementation, and testing stages. The assessment was based on four criteria: egg weight (35%), egg size (10%), storage time (25%), and eggshell color scale (30%). The system was implemented using Google Apps Script with Google Spreadsheet as the database. The implementation results show that the system is able to perform normalization, weighting, preference value calculation, and automatic ranking of duck egg quality. Blackbox Testing on seven main modules, namely login, alternative data, criteria data, weight setting, SAW calculation, ranking results, and report printing, showed that all modules functioned according to user requirements with a success rate of 100%. The results indicate that the SAW method can support duck egg quality assessment more objectively, consistently, and efficiently than manual assessment, thereby assisting decision-making for farmers and salted egg SMEs in Nganjuk Regency.